The Types of Discrimination and Princess Diana’s Ways to Pursue Her Freedom in Spencer (2021) - Salma, Nabila; Nirwan, Nirwan; Ramadhina, Retno (STIBA IEC JAKARTA, 2024)
This article elaborates the film